Police Human Resources Management in Brebes, Indonesia, to Increase the Disclosure of Child Sexual Violence Cases - Guntur Muhammad Tariq; Chairul Muriman Setyabudi; Yopik Gani (Journal of Social Research, 2025)
The purpose of this study is to analyze police human resources governance in revealing child sexual violence cases; and to describe the ideal design in handling cases of child sexual violence limited to the Brebes Police. This study uses a qualitative approach. Procedurally in handling reports of sexual violence against children, PPA Unit Investigators conduct analysis using counseling methods through cognitive interviews. The obstacles experienced in handling sexual violence against children start from: First, legal obstacles where there are challenges in implementing the TPKS Law against victims of electronic-based sexual violence. Second, obstacles from law enforcement factors, especially related to the perspective of investigators regarding the formal legal aspects of evidence, especially from victim witness statements, are sometimes considered by investigators not to meet the requirements as evidence. Third, obstacles from the facility factor are in the form of the absence of an Integrated "One Roof" service. Fourth, obstacles from patriarchal culture in the community and the taboo of understanding early sexual education. Finally, the obstacle of the "victim blaming" attitude by the community. The ideal design in handling cases of child sexual violence who experience psychological trauma from the legal side is the need for the formation of a Government Regulation based on Article 46 paragraph (1) concerning the deletion and/or termination of access to electronic information and/or documents.